Orthographic and Phonological Processing in Chinese Character Copying – A Preliminary Report - Lau, Dustin Kai-Yan (Frontiers in Psychology, 2020)
In the current study, the effects of orthographic and phonological processing in Chinese character copying were investigated using a data set extracted from a database containing handwriting data of 856 stimuli, the responses of which were collected from 100 participants. To investigate the effect of character frequency, radical frequency, and phonetic regularity, 151 phonetic compounds were selected from the database because (1) their corresponding phonetic radicals were all free-standing characters, (2) their corresponding phonetic radicals were located at either the right or the bottom positions in the characters, and (3) no more than 10% of the participants made errors when copying these target characters. The results of the linear mixed effect models revealed that after controlling for inter-stroke distance (ISD) and stroke number, the inter-stroke intervals (ISIs) at the radical and logographeme boundaries were significantly longer, indicating significant orthographic processing in the immediate copying task that radicals and logographemes were used as writing units. In addition, shorter ISIs at the logographeme boundary associated with higher radical frequency, and shorter ISIs at the radical boundary associated with higher character frequency and regular characters, were observed. These observations indicated significant orthographic and phonological effects in the immediate copying task. Finally, the significant phonetic regularity effect observed also supported the notion that phonology contributes to Chinese character writing, and that the effects of central processing, including character frequency and phonetic regularity, cascade over peripheral processing during Chinese character copying.